Breastfeeding practices in neonatal wards in Spain. Neo-BFHI international survey - Marta Cabrera-Lafuente; Clara Alonso-Díaz; Maria Teresa Moral Pumarega; Mariana Díaz-Almirón; Laura N. Haiek; Ragnhild Maastrup; Carmen Pallás-Alonso (Elsevier, 2022)
Introduction: In 2017, a worldwide survey was conducted on compliance with the practices promoted by Neo-BFHI (Baby-friendly Hospital Initiative expansion to neonatal wards). Objective: To present the results of the Spanish wards that participated in the global survey and compare them with those obtained internationally. Material and methods: Cross-sectional study through a survey on compliance with the Neo-BFHI ("Three basic principles", "Ten steps adapted to neonatal wards" and "the compliance with the International Code of Marketing of Breast-milk Substitutes" and subsequent relevant World Health Assembly resolutions). Compliance was calculated as the mean in each indicator and a final mean score for each neonatal unit. For the partial and final scores for each country and at the international level, the median was used. All scores ranged between 0 and 100. Results: The response rate in Spain was 90%. The range of the national mean for neonatal wards were from 37 to 99, with no differences in the final score according to the level of care. The global score for Spain (72) is below the international median (77) and this also occurs in 8 of 14 items. The neonatal wards from BFHI designated hospitals, obtained a significantly higher mean global score, and in 9 of 14 items than the non-accredited ones. Conclusions: Both international and national results indicate an improvement in breast feeding practices in neonatal units. The benefits of the BFHI accreditation of maternity reach neonatal wards. Spain has several key points below the international score. Resumen: Introducción: En 2017 se realizó una encuesta a nivel mundial sobre el cumplimiento de las prácticas que promueve la Neo-IHAN (Iniciativa para la Humanización de la Asistencia al Nacimiento y la Lactancia en las unidades neonatales). Objetivo: Presentar los resultados de las unidades españolas que participaron en la encuesta mundial y compararlos con los obtenidos internacionalmente. Material y métodos: Estudio transversal mediante una encuesta sobre el cumplimiento de los requisitos de la Neo-IHAN ("Tres principios básicos", "Diez pasos adaptados a unidades neonatales" y "el Cumplimiento del Código Internacional de Comercialización de Sucedáneos de Leche Materna"). El cumplimiento se calculó como la media en cada indicador y una puntuación media final para cada unidad neonatal. Para las puntuaciones parciales y finales de cada país y a nivel internacional se utilizó la mediana. Las puntuaciones van de 0 a 100. Resultados: La tasa de respuesta en España fue del 90% de las unidades de nivel 2 y 3. El rango de la media para las unidades neonatales fue de 37 a 99, sin diferencias según el nivel asistencial. La puntuación global de España (72) está por debajo de la mediana internacional (77) así como en 8 de los 14 requisitos de la Neo-IHAN. Las unidades neonatales de hospitales con maternidades acreditadas IHAN, obtuvieron una puntuación media final significativamente mayor así como en 9 de los 14 requisitos frente a las no acreditadas. Conclusiones: Los resultados tanto internacionales como nacionales indican una mejora de las prácticas de la lactancia materna en las unidades neonatales. Los beneficios de la acreditación IHAN de las maternidades alcanzan a las unidades neonatales. España tiene varios puntos clave por debajo de la puntuación internacional.